Toll-like receptor 2 and 6 agonist fibroblast-stimulating lipopeptide increases expression and secretion of CXCL1 and CXCL2 by uveal melanocytes. (March 2022) - Hu, Dan-Ning; Zhang, Ruihua; Iacob, Codrin E.; Yao, Shen; Yang, Shun-Fa; Chan, Chi-Chao; Rosen, Richard B.
Abstract: Fibroblast-stimulating lipopeptide (FSL-1) can activate Toll-like receptor 2 and 6 (TLR2/6), which recognize relevant molecules from gram-positive pathogens, fungus, and mycoplasma, and elevates the expression of CXCL1 and CXCL2, neutrophil chemoattractants, in certain types of cells. This effect has not previously been reported in the uveal melanocytes (UM). This study was designed to test the hypothesis that FSL-1 can induce the expression and secretion of CXCL1 and CXCL2 via activation of TLR2/6 in cultured human UM and producing an acute non-infectious uveitis reaction in the mouse. Flow cytometry and fluorescent immunostaining were used to measure the effect of FSL-1 on the expression of TLR2/6 in UM. Real time PCR and ELISA analysis were used to assess the ability of FSL-1 to elevate CXCL1/CXCL2 levels in cell lysates and conditioned media of UM, respectively. Flow cytometry measured phosphorylated MAPK and activated NF-κB signals in UM, with and without FSL-1 treatment. ELISA analysis tested the impact of various signal inhibitors (NF-κB, p38 MAPK, JNK1/2 and ERK1/2) and TLR2/6 antagonists on FSL-1-induced CXCL1/CXCL2 levels in cultured UM. The effects of neutralizing antibodies to TLR2 on FSL-1-induced mouse uveitis were tested in an experimental animal model. FSL-1 induced the expression of TLR2/6 proteins in cultured UM. FSL-1 significantly elevated the CXCL1 and CXCL2 proteins and mRNA levels in cultured UM time- and dose-dependently. FSL-1 mainly activated NF-κB, JNK, and expression of TLR2. FSL-1-induced expression of CXCL1 and CXCL2 was blocked by NF-κB, JNK, ERK inhibitors and TLR2 antagonists. Intravitreal injection of FSL-1 induced acute non-infectious mouse uveitis, which was significantly reduced in severity by a TLR2 antagonist. These results suggest that UM may play a role in the immune reaction, which targets invading pathogens, especially gram-positive bacteria. On the other hand, an excessive reaction to molecules from gram-positive bacteria may promote an inflammatory state of non-infectious uveitis. Highlights: FSL-1 (TLR2/6 agonist) activates TLR2 and TLR6 in cultured uveal melanocytes (UM). FSL-1 increases CXCL1/2 expression via JNK and NF-κB signal pathways in UM. Invitreal injection of FSL-1 induces acute noninfectious uveitis in the mouse. TLR2 antagonist inhibits FSL-1-induced mouse uveitis. UM may participate in immune response against gram-positive bacterial infection.